2017
DOI: 10.1002/aqc.2754
|View full text |Cite
|
Sign up to set email alerts
|

Whale‐watching trips in Peru lead to increases in tourist knowledge, pro‐conservation intentions and tourist concern for the impacts of whale‐watching on humpback whales

Abstract: 1. Since the implementation of the commercial whaling ban in the 1980s, whale-watching has become the most important economic activity involving whales worldwide.2. Whale-watching is promoted as a platform for education and conservation awareness of marine biodiversity. In Peru, where cetacean species are still in jeopardy, whale-watching may play an important part in promoting the protection of these species.3. This study aimed to determine the degree of whale-watching tourists' knowledge regarding cetacean e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 41 publications
3
42
1
3
Order By: Relevance
“…Potential negative impacts of whale watching activities have been reported to be derived from disturbance reasons, with consequent stress index increases and behavioral changes (Magalhaes et al, 1999;Erbe, 2002;Lusseau, 2006;Richter et al, 2006;Visser et al, 2011;Parsons, 2012;New et al, 2015). At the same time, it has been demonstrated that whale-watching can be an effective tool to raise awareness about species conservation issues and to educate tourists on cetaceans' ecology and threats, especially when the tourist experience is enriched by good environmental education (Lien, 2001;Lück, 2003;Stamation et al, 2007;Wearing et al, 2014;García-Cegarra and Pacheco, 2017;La Manna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Potential negative impacts of whale watching activities have been reported to be derived from disturbance reasons, with consequent stress index increases and behavioral changes (Magalhaes et al, 1999;Erbe, 2002;Lusseau, 2006;Richter et al, 2006;Visser et al, 2011;Parsons, 2012;New et al, 2015). At the same time, it has been demonstrated that whale-watching can be an effective tool to raise awareness about species conservation issues and to educate tourists on cetaceans' ecology and threats, especially when the tourist experience is enriched by good environmental education (Lien, 2001;Lück, 2003;Stamation et al, 2007;Wearing et al, 2014;García-Cegarra and Pacheco, 2017;La Manna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of surveys and interviews is an alternative method, which has the advantages of being relatively fast and less costly than traditional methods (Moore et al, 2010;Braulik et al, 2018). This method has been successful in generating information on dolphins and the effect of ecotourism (Walpole and Goodwin, 2010;Cegarra and Pacheco, 2017), on community perceptions toward dolphins and other species (Dowling, 1993;Dawson et al, 2004;Scott and Parsons, 2005) as well as in generating information on interactions with fisheries (Avila et al, 2008;Antunes Zappes et al, 2013;Quintana-Rizzo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although, there have been efforts to transmit this conduct code to all whale‐watching operators in the region, it is not clear whether all boats normally follow the conduct code. Therefore, it is important to assess whether whale‐watching is affecting humpback whale behavior, particularly when this activity has been promoted as an alternative to whaling and a potential tool to foster species and environmental conservation (Garcia‐Cegarra and Pacheco ).…”
mentioning
confidence: 99%